Estabilidade dinâmica de caminhada em pacientes com doença arterial periférica - Silva, Gaspar Guatimozin; Moraes, Daniel Umpierre de; Moraes, Ruy Silveira; Peyré-Tartaruga, Leonardo Alexandre; Figueiredo, Paula (Clinical and biomedical research. Porto Alegre, 2016)
n/a
n/a